4q+2(3q-8)=-q-6

Simple and best practice solution for 4q+2(3q-8)=-q-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4q+2(3q-8)=-q-6 equation:


Simplifying
4q + 2(3q + -8) = -1q + -6

Reorder the terms:
4q + 2(-8 + 3q) = -1q + -6
4q + (-8 * 2 + 3q * 2) = -1q + -6
4q + (-16 + 6q) = -1q + -6

Reorder the terms:
-16 + 4q + 6q = -1q + -6

Combine like terms: 4q + 6q = 10q
-16 + 10q = -1q + -6

Reorder the terms:
-16 + 10q = -6 + -1q

Solving
-16 + 10q = -6 + -1q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add 'q' to each side of the equation.
-16 + 10q + q = -6 + -1q + q

Combine like terms: 10q + q = 11q
-16 + 11q = -6 + -1q + q

Combine like terms: -1q + q = 0
-16 + 11q = -6 + 0
-16 + 11q = -6

Add '16' to each side of the equation.
-16 + 16 + 11q = -6 + 16

Combine like terms: -16 + 16 = 0
0 + 11q = -6 + 16
11q = -6 + 16

Combine like terms: -6 + 16 = 10
11q = 10

Divide each side by '11'.
q = 0.9090909091

Simplifying
q = 0.9090909091

See similar equations:

| 3x+3.4=7.3 | | 4x/3=24/5 | | 2+(-9)=x | | 10+h=1 | | -5n-(2n-4)=-2n-9 | | 4(3)+3(4)=19 | | (8-4)-4*2+1= | | 8x+19=5x+76 | | 8k-6(1+k)=5 | | 8x-12y=0 | | 4(1)+3(4)=19 | | 4(-7a+2)+10=-6+8a | | 4(n+1)=(11-n) | | 6*8-(3-7)+8*3= | | w^2=54 | | 4(6)+(-6)=-24 | | inx=-3 | | 7=w+7/7+4w-3/5 | | a(6)-2(-6)=-12 | | 9=5n-1 | | 3-2x=4x+1 | | -93-10=8x+15 | | 3=39y | | 3x-2(2-2x-8)=72 | | k/3=8 | | -44-(-99)= | | 7(n-5)-(2-3n)=9n | | 96=6u | | 4y+3x=5fory | | 4-12y+9y^2=0 | | s-1=22 | | -1=10z-4 |

Equations solver categories